Soil N Fluxes in Three Contrasting Dry Tropical Forests - Naoko Tokuchi; Asami Nakanishi; Chongrak Wachirinrat; Hiroshi Takeda (The Scientific World Journal)
A comparative study of N fluxes in soil among a dry dipterocarp forest (DDF), a dry evergreen forest (DEF), and a hill evergreen forest (HEF) in Thailand was done. N fluxes in soil were estimated using an ion exchange resin core method and a buried bag method. Soil C and N pools were 38 C Mg/ha/30 cm and 2.5 N Mg/ha/30 cm in DDF, 82 C Mg/ha/30 cm and 6.2 N Mg/ha/30 cm in DEF, and 167 C Mg/ha/30 cm and 9.3 N Mg/ha/30 cm in HEF. Low C concentration in the DDF and DEF sites was compensated by high fine soil content. In the highly weathered tropical soil, fine soil content seemed to be important for C accumulation. Temporal and vertical fluctuations of N fluxes were different among the sites. The highest N flux was exhibited at the onset of the wet season in DDF, whereas inorganic N production and estimated uptake of N were relatively stable during the wet season in DEF and HEF. It is suggested that N cycling in soil becomes stable in dry tropical forests to intermediate in temperate forests. N deposition may result in large changes of N cycling in the DDF and DEF due to low accumulations of C and N.